Arrayed telecom-wavelength compatible THz n-i-pn-i-p superlattice photomixers for spectroscopy applications - Preu, Sascha; Bauerschmidt, Sebastian; Malzer, Stefan; Döhler, Gottfried; Lu, Hong; Gossard, Art; Wang, Lijun (Terahertz and Midinfrared Radiation, 2011)
We report on the progress of room-temperature operating, continuous-wave, tunable n-i-pn-i-p superlattice THz photomixers, compatible with 1.55μm telecom laser systems. An output power of 0.65μW at 1THz has been achieved at a photocurrent of 9.5mA, using a broadband antenna. The spectral power is at a level where high resolution spectroscopy becomes attractive. This is demonstrated by measuring the absorption spectrum of water vapor between 0.4 and 1.6THz. We constructed an array of 4 mutually coherent photomixers for higher output power and spatial resolution. The interference of the four individual beams was measured in the target plane at a stand-off distance of 4.2m. We report on both a small THz spot diameter along the array axis of<1cm for ν>0.3THz and a high intensity of the central interference peak, in excellent agreement with numerical simulations. These features are very attractive for stand-off imaging and spectroscopy. © 2011 Springer Science+Business Media B.V.